2009
DOI: 10.1111/j.1365-2443.2009.01341.x
|View full text |Cite
|
Sign up to set email alerts
|

FLR‐2, the glycoprotein hormone alpha subunit, is involved in the neural control of intestinal functions in Caenorhabditis elegans

Abstract: The intestine plays an essential role in organism-wide regulatory networks in both vertebrates and invertebrates. In Caenorhabditis elegans, class 1 flr genes (flr-1, flr-3 and flr-4) act in the intestine and control growth rates and defecation cycle periods, while class 2 flr genes (flr-2, flr-5, flr-6 and flr-7) are characterized by mutations that suppress the slow growth of class 1 flr mutants. This study revealed that flr-2 gene controls antibacterial defense and intestinal color, confirming that flr-2 reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
41
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 32 publications
9
41
0
Order By: Relevance
“…The ortholog FSHR-1 is involved in innate immunity, stress responses, and germline fertility (69)(70)(71). The C. elegans genome also encodes two genes, flr-2 and T23B12.8, for α and β glycoprotein subunits (72,73). It will be interesting to see whether TRH-like signaling regulates the release of invertebrate glycoproteins, similar to its function in vertebrates, or whether its role in these species points to a different ancestral function.…”
Section: Discussionmentioning
confidence: 99%
“…The ortholog FSHR-1 is involved in innate immunity, stress responses, and germline fertility (69)(70)(71). The C. elegans genome also encodes two genes, flr-2 and T23B12.8, for α and β glycoprotein subunits (72,73). It will be interesting to see whether TRH-like signaling regulates the release of invertebrate glycoproteins, similar to its function in vertebrates, or whether its role in these species points to a different ancestral function.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it was not clear from these papers whether GPA2 and GPB5 were chemically cross-linked in GPA2/GPB5 heterodimers used in the bioactivity studies. Thus, it cannot be ruled out that GPA2 and/or GPB5 exert biological functions of their own (48, 49). …”
Section: Structure Of Glycoprotein Hormones and Their Ancestorsmentioning
confidence: 99%
“…In Caenorhabditis elegans , only one GPCR gene with LRRD has been identified ( fsh-r1 ) that exhibits the highest similarity with FSHR among mammalian GPHR and plays a role in innate immune response (110). In this species, genes apparented to GPA2 ( flr-2 ) and GPB5 ( flr-5 ) were identified and might regulate FSH-R1 in the neural control of intestinal functions (49), maybe including intestinal ion-transport and/or intestinal immune defense.…”
Section: Molecular Mechanisms Of Action Of Glycoprotein Hormonesmentioning
confidence: 99%
“…Their endogenous physiological function, however, remains to be elucidated. These hormones are attributed various functions in the gut in D. melanogaster (Sellami et al, 2011) and C. elegans (Oishi et al, 2009), including antibacterial defense, intestinal color change, defecation cycling, and possible water reabsorption. A putative function for LH in the gut during development could thus represent an evolutionarily redundant glycoprotein function, whereas in higher vertebrates Gpa2 and Gpb5 could possibly have assumed a thyrotropic function.…”
Section: Developmental Dynamicsmentioning
confidence: 99%
“…As these proteins are found in invertebrates, it has been suggested that they represent an ancestral glycoprotein (Roch et al, 2011). In addition to a putative thyrotropic effect in mammals, GPB5 and GPA2 have been suggested to function as an insect anti-diuretic hormone (Sellami et al, 2011) and to act as a neural signaling molecule controlling intestinal function in nematodes (Oishi et al, 2009). …”
Section: Introductionmentioning
confidence: 99%